Measuring international capital mobility : recent evidence from alternative tests - Anthony, Myrvin ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Updates some of the available evidence on the degree of international capital mobility. Examines recent data on domestic (onshore] and Eurocurrency (offshore) interest rates for five OECD countries to assess how close these rates are.